SIFAT VENIR DAN KAYU LAPIS ENAM JENIS KAYU DARI IRIAN JAYA - M I Iskandar; Suwandi Kliwon; Paribntro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
A study result on the suitability of wood species from Irian Jaya as raw material for veneer and plywood is reported in this paper. This study consisted log peeling characteristic, veneer property, some physical and mechanical properties of plywood (triplex and multiplex).All of the logs from 6 wood species could be peeled in cold condition, producing 1.5 mm veneer at a cutting angle between 920-92°30-The average shrinkage of veneer is 7.99%, with a minimum of 6. 74% (sehiega) and maximum of 9. 71 % (petuon). Veneer swelling from oven-dry to air-dry condition varied between 2. 68% (katulampa) and 4.01 % (petuon) with an average of 3.19%.The bonding strength of plywood for type 11 from 6 wood species (100%) conform's with the Indonesian Standard6 wood species (100%) with Japanese Standard and 6 species (100%) with German Standard.The specific gravity of multiplex is higher than triplex. Some mechanical properties of multiplex are higher than triplex